Agreeableness as Predictor of Induced Scratching in Patients with Atopic Dermatitis: A Replication Study - Schut, Christina; Reinisch, Katharina; Classen, Alexander; Andres, Sarah; Gieler, Uwe; Kupfer, Jörg; Justus Liebig University Giessen (My University, 2018)
In patients with atopic dermatitis agreeableness and public self-consciousness have previously been shown to be significant predictors of induced scratching, while depression was significantly related to induced itch. This study aimed to replicate these findings. Itch and scratching were induced by videos of crawling insects or skin diseases. Induced itch was measured using a visual analogue scale. Scratching behavior was evaluated by two raters. Psychological variables were assessed using validated questionnaires. Induced scratching could be predicted significantly by agreeableness (corrected R2 = 15.5% or 38 % after exclusion of one outlier): Patients scoring low on agreeableness showed a higher increase in scratch movements than patients scoring high on this scale. No associations between induced scratching/itch and public self-consciousness/depression were found. One clinical implication that arises from this study could be to offer patients scoring low on agreeableness certain psychological interventions.
Keywords: atopic dermatitis; itch; scratching; personality; agreeableness; ddc:610